2017
DOI: 10.1080/15548627.2017.1358848
|View full text |Cite
|
Sign up to set email alerts
|

Restoring diabetes-induced autophagic flux arrest in ischemic/reperfused heart by ADIPOR (adiponectin receptor) activation involves both AMPK-dependent and AMPK-independent signaling

Abstract: Macroautophagy/autophagy is increasingly recognized as an important regulator of myocardial ischemia-reperfusion (MI-R) injury. However, whether and how diabetes may alter autophagy in response to MI-R remains unknown. Deficiency of ADIPOQ, a cardioprotective molecule, markedly increases MI-R injury. However, the role of diabetic hypoadiponectinemia in cardiac autophagy alteration after MI-R is unclear. Utilizing normal control (NC), high-fat-diet-induced diabetes, and Adipoq knockout (adipoq) mice, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 44 publications
1
36
0
1
Order By: Relevance
“…Autophagy is inhibited in type 2 diabetes mellitus, whereas it is activated in type 1 diabetes mellitus 32 . The reasons for these inconsistencies are as follows: (i) different methods of autophagy detection lead to different interpretations of the results 33 ; and (ii) the impairment of autophagy varies at different stages of diabetes. In the preliminary experiment, we also found that autophagy was inhibited with 24 h high glucose treatment, but overactivated if treated with high glucose for 72 h. This might be the reason why autophagy has different roles in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is inhibited in type 2 diabetes mellitus, whereas it is activated in type 1 diabetes mellitus 32 . The reasons for these inconsistencies are as follows: (i) different methods of autophagy detection lead to different interpretations of the results 33 ; and (ii) the impairment of autophagy varies at different stages of diabetes. In the preliminary experiment, we also found that autophagy was inhibited with 24 h high glucose treatment, but overactivated if treated with high glucose for 72 h. This might be the reason why autophagy has different roles in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…AdipoRON effectively improved insulin sensitivity and restored glucose homeostasis via the activation of AdipoR1-AMPK-PGC1α and AdipoR2-PPARα signaling pathways (162). AdipoRON treatment also mimicked adiponectin's established anti-diabetic effects (163) and ability to enhance cellular capacity for mitigating oxidative-stress (162,164), enhancing lipid/glucose oxidation in mitochondria (162,164), anti-inflammatory responses (162,(164)(165)(166)(167), lifeprolonging effect (162,163), anti-cancer effects (168,169), procell survival and anti-apoptotic effect (170,171), neuronal- (172,173), reno- (174,175), and cardio-/vascular-protective effects (165,(176)(177)(178)(179). However, exciting AdipoRON research in animal models has not been translated to establishment of a drug for human use and the search continues for additional small molecule AdipoR agonists which have little or no toxicity.…”
Section: Adiporonmentioning
confidence: 95%
“…AdipoRon, via AMPK, stimulated the formation of these autophagosomes, increasing clearance, reducing infarction area, and improving cardiac function. (23,24) On the other hand, Zhang et al, stated that APN antioxidative and anti-inflammatory role does not occur via AMPK, but via protein kinase A (PKA). The researchers suggested that, when they administered APN 10 minutes before promoting IRS in the heart muscle, there was a decrease in oxidative stress and a reduction of the infarcted area in the study group.…”
Section: ❚ Discussion Adiponectin and Ischemia-reperfusion Syndrome Imentioning
confidence: 99%
“…AdipoRon, via AMPK, stimulated the formation of these autophagosomes, increasing clearance, reducing infarction area, and improving cardiac function. ( 23 , 24 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation